Intestinal Dysbiosis and Tryptophan Metabolism in Autoimmunity - Brown, Josephine; Robusto, Brian; Morel, Laurence (Frontiers in Immunology, 2020)
The development of autoimmunity involves complex interactions between genetics and environmental triggers. The gut microbiota is an important environmental constituent that can heavily influence both local and systemic immune reactivity through distinct mechanisms. It is therefore a relevant environmental trigger or amplifier to consider in autoimmunity. This review will examine recent evidence for an association between intestinal dysbiosis and autoimmune diseases, and the mechanisms by which the gut microbiota may contribute to autoimmune activation. We will specifically focus on recent studies connecting tryptophan metabolism to autoimmune disease pathogenesis, and we will discuss evidence for a microbial origin. This will be discussed in the context of our current understanding of how tryptophan metabolites regulate immune responses, and how it may, or may not, be applicable to autoimmunity.